2013
DOI: 10.1111/acer.12278
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Disulfiram for the Treatment of Alcohol Dependence Assessed with a Multicenter Randomized Controlled Trial

Abstract: Supervised oral disulfiram use followed by intervention via letters seems to be ineffective for increasing abstinence. Further studies are necessary to prove the efficacy of disulfiram for the pharmacological treatment of alcohol dependence. We indicated the effectiveness of disulfiram for the maintenance of abstinence in patients with inactive ALDH2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
1
17
0
6
Order By: Relevance
“…Similarly, in humans, the success rate of treatment with disulfiram is quite low because many patients do not show aversion to ethanol ingestion and further develop tolerance to disulfiram. Recent placebo-controlled clinical work and meta-analyses also show that disulfiram—as a drug (in blind studies)—is not different from placebo in reducing ethanol relapse in alcoholics (Skinner et al, 2014; Yoshimura et al, 2014). These studies might be taken as an indication that following chronic ethanol intake a systemic elevation of acetaldehyde does not inhibit ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in humans, the success rate of treatment with disulfiram is quite low because many patients do not show aversion to ethanol ingestion and further develop tolerance to disulfiram. Recent placebo-controlled clinical work and meta-analyses also show that disulfiram—as a drug (in blind studies)—is not different from placebo in reducing ethanol relapse in alcoholics (Skinner et al, 2014; Yoshimura et al, 2014). These studies might be taken as an indication that following chronic ethanol intake a systemic elevation of acetaldehyde does not inhibit ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…One recent exception involves disulfiram, a pharmacologic antagonist of ALDH2, the effects of which mimick those of the null ALDH2 allele. Yoshimura et al (2014) found that, in a small subsample of individuals treated with disulfiram, the presence of the ALDH2 variant was associated with a higher rate of abstinence from alcohol. A moderator effect of the ALDH2 variant variant has also been demonstrated in a human alcohol challenge study (Peng et al, 2014).…”
Section: Pharmacogenetics Of Subjective Effects Associated With Alcohmentioning
confidence: 90%
“…In a medium-risk-of-bias trial conducted in Japan (Yoshimura et al 2014), subjects (total N=109) were randomly assigned according to a 2×2 design with disulfiram 200 mg/day vs. placebo and receipt of educational material on drinking harms and craving management vs. no such education. At 26 weeks, there were no differences among groups in the percent of individuals who remained abstinent.…”
Section: Benefits Of Disulfirammentioning
confidence: 99%